1985
DOI: 10.1111/j.1365-2621.1985.tb10475.x
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Muscle Alkaline Proteinase in the Textural Degradation of Fish Meat Gel

Abstract: Unlike the actomyosin paste, white croaker meat paste showed poor elastic gel when heated around 60°C. The hydrolysis of muscle protein by muscle proteinase was observed in the poor gel. There are at least four kinds of proteinases in white croaker muscle: cathepsin D, neutral proteinase, calpain and alkaline proteinase. Among them only alkaline proteinase could act at pH of meat paste and around 60°C. Above facts confirmed the previous work that the heat-stable alkaline proteinase is probably implicated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 22 publications
0
29
0
2
Order By: Relevance
“…The effect of the substrates on enzyme activity was determined by adding 250 μL of enzyme solution to 250 μL of 1 mM or 1% substrates; azocasein (Ninojoor and Srivastava 1985), casein (Makinodan et al. 1985), BSA (Doke and Ninojoor 1987), N‐α‐benzoyl‐L‐Arg‐p‐nitroanilide (Oliveria et al.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the substrates on enzyme activity was determined by adding 250 μL of enzyme solution to 250 μL of 1 mM or 1% substrates; azocasein (Ninojoor and Srivastava 1985), casein (Makinodan et al. 1985), BSA (Doke and Ninojoor 1987), N‐α‐benzoyl‐L‐Arg‐p‐nitroanilide (Oliveria et al.…”
Section: Methodsmentioning
confidence: 99%
“…The shrimp enzyme had an optimum temperature of 60°C and remained partially active even after exposure to 80°C. Apart from exogenous substrates alkaline proteinase is capable of degrading myofibrillar proteins (Lin and Lanier, 1980;Folco et al, 1984) and, therefore, is implicated in the textural degradation of minced fish meat (Deng 1981;Lanier et al, 1981;Makinodan et al, 1985). Although myofibrillar proteins were not used as substrates in the present study, shrimp muscle alkaline proteinasc seemed to be capable of degrading all protein substrates with the exception of bovine serum albumin.…”
Section: Discussionmentioning
confidence: 73%
“…Heat‐stable alkaline protease has often been reported to be responsible for textural degradation of surimi gels. Makinodan et al 24 reported that only alkaline protease could act at the pH of meat paste and 60 °C. Alkaline protease from white croaker had optimum activity at 60 °C and pH 8.0 25.…”
Section: Resultsmentioning
confidence: 99%